The lived experience of parents of children admitted to the pediatric intensive care unit in Lebanon - Doumit, Myrna A.A. (2014)
Background Family caregivers have a significant responsibility in the care of their child in the Pediatric Intensive Care Unit (PICU). Parents staying with their child in the PICU have particular needs that should be acknowledged and responded to by clinicians. Several studies have been conducted in the USA and Europe to try to understand the experience of family caregivers of children admitted to the Pediatric Intensive Care Unit. There are no such studies in Lebanon or the Middle East where the culture and support systems differ from other countries. Objective To understand the lived experience of Lebanese parents of children admitted to the PICU in a tertiary hospital in Beirut. Design Phenomenological study. Methods The study followed purposeful sampling in which 10 parents (mother or father) of children admitted to PICU were interviewed. Data were analyzed following the hermeneutical process as described by Diekelmann and Ironside (1998). Results A constitutive pattern “Journey into the unknown” which constitutes an overarching theme and four major themes with subthemes emerged from the data. These were: We are human beings with dignity “; “looking for a healthier environment”; Dependence on God and “The need to be in the loop” reveal the parents’ journey into the unknown. Conclusion This qualitative study adds to the knowledge that would help health care workers understand the experience of Lebanese parents with a child in PICU and to highlight the significance of this experience to them. The findings could be used to inform the development of a PICU parental satisfaction instrument for the sample group.